TEACHER AGENCY IN INTEGRATING PANCASILA VALUES INTO ENGLISH LANGUAGE TEACHING: PERSPECTIVES AND CHALLENGES FROM RURAL INDONESIA - Santi Farmasari; Desi Herayana; Hartati Suryaningsih; La Ode Alfin Aris Munandar; Aril Eka Rizki; Alzena Aristawidya (Universitas HKBP Nommensen, 2026)
This study examines the agency of English teachers in incorporating the Pancasila Student Profile (PSP) values into English Language Teaching (ELT) under Indonesia's Independent Curriculum. Despite the PSP's major role in curriculum reform, there is less understanding of how EFL teachers exert agency in implementing national character education objectives within language teaching methods, especially in rural settings. This qualitative study, informed by the ecological concept of teacher agency, included ten English teachers from five regencies on Lombok Island, Indonesia. Data were gathered through semi-structured interviews, narrative reflections, and document analysis, and were examined using thematic analysis. The findings indicate that instructors viewed PSP integration to assert agency through pedagogical decision-making, multidisciplinary cooperation, and instructional innovation. Nonetheless, their agency was hindered by restricted curricular understanding, inadequate assessment literacy, workload demands, and financial constraints. This study enhances the literature on teacher agency by illustrating how agency is simultaneously facilitated and restricted by personal, structural, and relational factors during curricular reform. The results underscore the necessity for ongoing professional development, collaborative educational environments, and supporting institutional policies to enhance teachers' ability to incorporate national values into English Language Teaching.